Optimalisasi Pemanfaatan Ruang Luar Kampus ITSB Deltamas Melalui Penelitian Persepsi dan Harapan Sivitas Akademik - Esti Galuh Arini (JOURNAL OF APPLIED SCIENCE (JAPPS), 2020)
Many college campuses in Indonesia are designed so that the academic civitas, especially students, feel at home in their activities. The length of stay of students on campus is one important factor in supporting the success of the learning process. Therefore, the design of the campus outdoor space in accordance with the expectations of its users must be considered to support this. For the case study, research was carried out at the Bandung Institute of Technology and Science (ITSB) in the City of Deltamas, Cikarang, West Java. In the near future ITSB Deltamas will have two new buildings: the Container Building as an additional classroom and the Student Dormitory Building, in addition to the Main Campus Building which is the place for all current academic activities now. However, the campus outdoor space has not been well planned, so the use of the space has not been optimal. Optimizing the use of offcampus space is obtained through research of perceptions and expectations aimed at formulating the needs and desires of the academic civitas of ITSB Deltamas by finding the types of activities and facilities that best suit the needs and desires of its users. The results of this study are the design criteria of the ITSB Deltamas outdoor space which can be a recommendation in the field of outdoor space supply planning as an integral part of future campus planning. It is expected that by creating programs and design criteria that meet the needs and desires of the ITSB Deltamas academic civitas as end users, it will create an outdoor campus space design that is responsive to wants and needs (responsive), has emotional ties (meaningful), and can be used by all users (democratic).